Administralivno-pravovoy of spores of kak kategoriya yuridicheskogo spor - Мацелик, Тетяна Олександрівна; Параниця, Сергій Павлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In this article the concept of administrativno-pravovogo dispute is formulated and his essence is certain.Questions in relation to the order of consideration of administrativno-pravovykh disputes purchased thespecial actuality not only in connection with an input in Ukraine of the administrative legal proceeding butalso because the existent mechanisms of their decision appear not enough effective, such, which do notprovide the persons of valuable realization of their right of defence.